¹⁸F-labeled silicon-based fluoride acceptors: potential opportunities for novel positron emitting radiopharmaceuticals. - Bernard-Gauthier, Vadim; Wängler, Carmen; Schirrmacher, Esther; Kostikov, Alexey; Jurkschat, Klaus; Wängler, Bjoern; Schirrmacher, Ralf (BioMed Research International, 2014)
Background: Over the recent years, radiopharmaceutical chemistry has experienced a wide variety of innovative pushes towards finding both novel and unconventional radiochemical methods to introduce fluorine-18 into radiotracers for positron emission tomography (PET). These "nonclassical" labeling methodologies based on silicon-, boron-, and aluminium-(18)F chemistry deviate from commonplace bonding of an [(18)F]fluorine atom ((18)F) to either an aliphatic or aromatic carbon atom. One method in particular, the silicon-fluoride-acceptor isotopic exchange (SiFA-IE) approach, invalidates a dogma in radiochemistry that has been widely accepted for many years: the inability to obtain radiopharmaceuticals of high specific activity (SA) via simple IE.Methodology: The most advantageous feature of IE labeling in general is that labeling precursor and labeled radiotracer are chemically identical, eliminating the need to separate the radiotracer from its precursor. SiFA-IE chemistry proceeds in dipolar aprotic solvents at room temperature and below, entirely avoiding the formation of radioactive side products during the IE.Scope Of Review: A great plethora of different SiFA species have been reported in the literature ranging from small prosthetic groups and other compounds of low molecular weight to labeled peptides and most recently affibody molecules.Conclusions: The literature over the last years (from 2006 to 2014) shows unambiguously that SiFA-IE and other silicon-based fluoride acceptor strategies relying on (18)F(-) leaving group substitutions have the potential to become a valuable addition to radiochemistry.